Analysis of Students' Metacognition Skills in Solving Problems in Wake Space Reviewed From Numeracy Skills - Siti Utami, Ety; Setyaningsih, Nining (JTMT: Journal Tadris Matematika, 2024)
This study aims to analyze students' metacognition skills in solving problems in geometric shapes in terms of numeracy abilities. In this study using descriptive qualitative method. Information sorting techniques involving instruments in the form of surveys of metacognition skills, tests structured as exposition questions regarding approved spatial forms and interviews to obtain information. In problem solving, students who have high metacognition skills are more thorough and precise starting from planning, monitoring, and evaluating. They take a long time to solve the problem, but the results obtained are correct or correct. Conversely, students who have low metacognition skills seem rushed and less thorough and begin with planning, monitoring and evaluation. Students who have low metacognition skills to solve problems have not been able to manage all activities and do not know what metacognitive activities are being carried out.